2016
DOI: 10.1128/jcm.02089-15
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology Analysis of Streptococcus pyogenes in a Hospital in Southern Taiwan by Use of the Updated emm Cluster Typing System

Abstract: g emm typing is the most widely used molecular typing method for the human pathogen Streptococcus pyogenes (group A streptococcus [GAS]). emm typing is based on a small variable region of the emm gene; however, the emm cluster typing system defines GAS types according to the nearly complete sequence of the emm gene. Therefore, emm cluster typing is considered to provide more information regarding the functional and structural properties of M proteins in different emm types of GAS. In the present study, 677 iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
3
4
0
1
Order By: Relevance
“…This is in accordance with previous reports completed by Sagar (40), Dhanda (41) and Arêas (42), that identified emm types belonging to cluster E6 (emm75, emm81) as the predominant isolates obtained from countries closely relating to the impoverished environments within Africa, India and Brazil respectively. However, when referring to invasive disease, the predominant emm clusters are E3, followed by E6 and D4, which is complimentary to the emm cluster data shown by Chiang-Ni (18).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is in accordance with previous reports completed by Sagar (40), Dhanda (41) and Arêas (42), that identified emm types belonging to cluster E6 (emm75, emm81) as the predominant isolates obtained from countries closely relating to the impoverished environments within Africa, India and Brazil respectively. However, when referring to invasive disease, the predominant emm clusters are E3, followed by E6 and D4, which is complimentary to the emm cluster data shown by Chiang-Ni (18).…”
Section: Discussionsupporting
confidence: 77%
“…Australia, Fiji and New Caledonia illustrated that 70%-84% of clusters from isolates were shared, as opposed to comparison of emm types having only 14%-30% commonality between countries (17). In a third study by Chang-Ni in Taiwan, an analysis of both invasive and non-invasive strains revealed that cluster E6 was associated with both types of infections, while clusters D4, E2 and E3 were responsible for causing invasive isolates in their population (18). Recently, Frost demonstrated that M type-specific and cross-reactive immune responses frequently align with emm clusters, raising new opportunities to design multivalent vaccines with broad coverage (19).…”
Section: Introductionmentioning
confidence: 96%
“…Among pharyngeal isolates, the seven most frequent emm clusters accounted for 98.5% of the emm typed isolates in this study. Other reports have shown similar results: 96.5% of those collected in a prospective study conducted in Western Greece between 1999 and 2005 [29], authors' unpublished data], 92.8% of 7,040 isolates in the USA [12] and 91.1% in Southern Taiwan [39]. High diversity of emm types has been observed in the Pacific region and other lowincome settings [11,40].…”
Section: Plos Onesupporting
confidence: 58%
“…Australia, Fiji, and New Caledonia, illustrated that 70% to 84% of clusters from isolates were shared, as opposed to comparison of emm types having only 14% to 30% commonality between countries ( 15 ). In a third study by Chiang-Ni et al in Taiwan, an analysis of both invasive and noninvasive strains revealed that cluster E6 was associated with both types of infections, while clusters D4, E2, and E3 were responsible for causing invasive isolates in their population ( 16 ). Recently, Frost et al demonstrated that M type-specific and cross-reactive immune responses frequently align with emm clusters, raising new opportunities to design multivalent vaccines with broad coverage ( 17 ).…”
Section: Introductionmentioning
confidence: 99%